Neurophysiological Driver Behavior Analysis - Kamaruddin, Norhaslinda; Abdul Rahman, Abdul Wahab; Alarabi, K.F.; Abut, Huseyin (Walter de Gruyter GmbH, 2020)
People behave differently even under similar situations especially when driving.This is due to their behavior, exposure, experience, and judgment when facing certain phenomena, which in turn affect their driving capability. Each individual has a set of unique patterns of personality traits that derive and influence the behavior. With the advancement of technology, personality traits have become measurable. Therefore, driver behavior can be predicted to a certain degree through the assessment of driver personality. Personality is determined by means of interviews or self-reported questionnaires. However, these approaches are very much dependent on the truthfulness and honesty of the participants when answering the questionnaires, as they may have the tendency to exaggerate or suppress the answers. Hence, an alternative approach of using input without biasness of participants is needed. In this work, we employed neurophysiological input from brain signals captured from electroencephalograms (EEG) to measure emotion and link this to the understanding of personality. This is to study the correlation between the behavior and emotion based on the hypotheses that emotion influences on behavior and personality are affected by behavior. Experimental results indicate that emotion can be measured using the proposed approach, with accuracy ranging from 60% to 99% for happiness, fear, sadness, and calmness. The conscientiousness in personality traits is then measured and analyzed. It is found that there is a negative correlation between the conscientiousness and valence for fear, making it possible to detect this trait. These findings can be extended to understand driver behavior, which potentially could lead to safer driving and avoiding accidents.